2010
DOI: 10.1083/jcb.201007013
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome and p97 mediate mitophagy and degradation of mitofusins induced by Parkin

Abstract: The Parkin ubiquitin ligase marks the mitofusins Mfn1 and Mfn2 for proteasome-dependent degradation, promoting disposal of damaged mitochondria by preventing their fusion with healthy organelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,145
8
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,223 publications
(1,212 citation statements)
references
References 57 publications
57
1,145
8
2
Order By: Relevance
“…66 Although similar studies in mammalian systems have produced contradictory results, 64,67 the findings in the fly indicate that PINK1 and Parkin promote fission. Consistent with this conclusion, mammalian and fly studies indicate that upon mitochondrial depolarization, Parkin translocates to mitochondria and causes polyubiquitination of Mitofusin, targeting it for removal from the mitochondrial membrane by the p97 AAA-ATPase and subsequent proteosomal degradation [55][56][57] ( Figure 4bi). Degradation of Mitofusin prevents damaged mitochondria from fusing with the functional mitochondrial network and is essential for their subsequent degradation by mitophagy.…”
Section: The Pink1/parkin Pathway Of Mitophagysupporting
confidence: 61%
See 2 more Smart Citations
“…66 Although similar studies in mammalian systems have produced contradictory results, 64,67 the findings in the fly indicate that PINK1 and Parkin promote fission. Consistent with this conclusion, mammalian and fly studies indicate that upon mitochondrial depolarization, Parkin translocates to mitochondria and causes polyubiquitination of Mitofusin, targeting it for removal from the mitochondrial membrane by the p97 AAA-ATPase and subsequent proteosomal degradation [55][56][57] ( Figure 4bi). Degradation of Mitofusin prevents damaged mitochondria from fusing with the functional mitochondrial network and is essential for their subsequent degradation by mitophagy.…”
Section: The Pink1/parkin Pathway Of Mitophagysupporting
confidence: 61%
“…However, although loss of Mitofusin is necessary for mitophagy to proceed, it is not by itself sufficient to trigger mitophagy and PINK1 and Parkin can initiate mitophagy in cells lacking Mitofusin. 56,68 Mitochondrial fragmentation in the absence of Mitofusin thus appears to be a permissive rather than a triggering event.…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PINK1 deficiency or point mutations induce mitochondrial fragmentation in immortal or primary human neuronal cells, indicating that PINK1 and Parkin inhibit mitochondrial fission in human neuronal cells (Exner et al, 2007;Kim et al, 2008a). Recently, several groups reported that the pro-mitochondrial fusion protein Marf and its human homolog, mitofusin (Mfn), are specifically ubiquitinated and degraded by Parkin in both human and Drosophila systems (Gegg et al, 2010;Tanaka et al, 2010;Ziviani et al, 2010). Therefore, the exact molecular mechanisms underlying these different mitochondrial remodeling patterns are expected to be elucidated soon.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 99%
“…When mitochondria are damaged by CCCP and lose membrane potential, the kinase PTEN-induced putative kinase protein 1 (PINK1) accumulates and recruits the E3 ubiquitin ligase parkin specifically to the damaged mitochondrion (41). Parkin ubiquitinates mitochondrial proteins including mitofusins, and they cause mitochondria to be engulfed by double-layered isolation membranes (42). Recent studies have indicated the existence of specific adaptors, such as p62 and NBR1, which link with the ubiquitinated targets to LC3-II of autophagosomal membranes (43,44).…”
Section: Ubiquitin-modified Peroxisomes Were Degraded Selectivelymentioning
confidence: 99%